ETHNIC IDENTITY IN URBAN AND RURAL SPACES: KEY INDICATORS OF HISTORICAL AND CULTURAL HERITAGE (ON THE EXAMPLE OF THE ALTAI KAZAKHS) - Anna D. Derendyaeva; Daria A. Mikhalevskaya (Sovremennye Issledovaniâ Socialʹnyh Problem)
Background. In recent years, the study of multinational regions of the Russian Federation has become relevant, in the development of which various strategies and practices are observed in preserving their historical and cultural heritage. At the same time, the study of local communities, namely individual ethnic groups, is of particular interest. It is becoming important to study how the institution of heritage influences the processes of identity formation in these communities, whether it differs in urban and rural environments.